Sosialisasi Kesadaran Lingkungan Dan Pengelolaan Sampah Dalam Peningkatan Perilaku Peduli Lingkungan Masyarakat Di Desa Durinan, Bangkalan - Rasti Nur Alfaisya Safitri (PT. Adriani Mandiri Publisher, 2026)
This community service activity aims to increase awareness and foster environmentally responsible behavior through waste management socialization in Durinan Village, Bangkalan Regency. The main problem faced by the community is the low level of understanding regarding the sorting and processing of household waste, which has traditionally been handled in simple ways, such as burning or disposing of it without proper management. This activity involved 9 participants consisting of housewives and village youth. The method used in this program is the Asset-Based Community Development (ABCD) approach, with data collection techniques including field observations, group discussions, and questionnaire distribution. This approach emphasizes the utilization of community assets as the foundation for program implementation. Through the socialization activities, participants were provided with an understanding of different types of waste, particularly organic and inorganic waste, as well as the importance of proper and sustainable waste management. The results show an improvement in community understanding of waste management. Based on questionnaire results, 2 participants demonstrated initial awareness of waste management, 3 participants began managing waste independently, and 4 participants reduced plastic usage and practiced sorting organic and inorganic waste at the household level. In addition, early behavioral changes were observed, such as the habit of separating waste and efforts to reduce plastic consumption. Active community participation throughout the program also served as an indicator of its success. However, behavioral change requires time and continuous support, both in terms of facilities and assistance. Therefore, this activity is effective as an initial step in building community-based environmental awareness and responsible behavior